Would introducing the domestic buffalo into Ethiopia be worthwhile? - Taye, T.; Ayalew, W. (Ethiopian Society of Animal Production, 2004)
The domestic buffalo occupies an important place amongst the domestic animals of the tropics as a provider of dairy produce, beef and draught power. As dairy animal under a small scale buffalo operation in India, the buffalo has a milk yield of 1000-1500 liters (1030-1545 kg) in about 200 days of lactation length, which surpassed the cow with average lactation yield of 238\B182 liters in 23.9\B155 days of lactation length under similar management system. The carcass dressing percentage of buffaloes ranges from 50 to 58, which is better than that of Small East African zebu, of 42 to 53 percent. As work (draught) animals buffaloes have longer working life than do indigenous cattle. Buffaloes have less discriminating foraging habit and therefore consume wider range of coarse fodder than have cattle. Dies makes them more suitable converters of particularly feeds of poor quality, with high cellulose. Domestic buffaloes adapt to a wide range of environmental conditions and they can easily acclimatize to same humid and sub humid areas of western Ethiopia as well as in igable fields in the Awash valley. However, buffaloes exhibit low reproductive efficiency and they are susceptible to certain diseases especially trypanosomosis. Thus, care should be taken in identifying suitable. areas for testing and promoting the buffalo. The constraints are not insurmountable, however. Countries of east and Southeast Asia have expertise and experience in profitable utilizatmn of the buffalo, and promotional activities in Ethiopia should draw lessons from them. It was therefore concluded that introducing the buffalo to selected parts of Ethiopia is worthwhile.